Analisis Desain Ramp Tambang pada PIT B PT Pancaran Surya Abadi Kabupaten Kutai Kartanegara - ramadhan shaddad, Aqsal; Nurwaskito, Arif (CV Insight Publisher, 2024)
Mining Design plays an important role in extracting reserves from mineral deposits. The mine design makes it easy to meet production targets and is ideal for horizontally shaped ore bodies such as coal. The purpose of this study is to determine the design of the ramp in the mining pit, determine the ramp pit and the type of ramp used. This research method uses mine planning surpac software and data processing excel software to make a ramp design, determine the type of ramp. The results of the research that has been carried out obtained a ramp design with the type of Constant berm ramp using a stepped geometry, namely the maximum overall slope of the high wall is 60° and the low wall is 45°, the step height is 8 m, and the step width is 3 m, the road width is 10 m, with a road grade of 12%. of these results assumes that the mine is theoretically free from landslides. So that the tool can work optimally both empty and loaded on an incline. The type of road used has the highest level of safety when compared to other types of mining roads.